(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : Vitamin D deficiency (VDD) is a widespread problem in developing countries. Recent studies have shown association of Vitamin D deficiency with atherosclerosis and Coronary artery disease. This study was conducted to assess the relationship between Vitamin D and the severity of coronary artery disease (CAD) in patients undergoing coronary angiography. Materials and methods: Consecutive patients who underwent coronary angiography for acute coronary syndrome or effort angina were included in a descriptive cross-sectional study and their Vitamin D level was measured. CAD was defined as at least one vessel stenosis >50% on coronary angiography. Vitamin D levels were correlated to the CAG findings as to the severity and number of vessels involved and also to the traditional CAD risk factors Results: Vitamin D Deficiency was noted in 70.72% of the population in the study. Patients were classified as normal Vitamin D level(> 30ng/ml), Vitamin D insufficiency (20-30ng/ml) and Vitamin D Deficiency (<20ng/ml). Vitamin D levels had inversely correlated with significant coronary artery disease both for number of vessels involved and severity (p<0.001) and dyslipidemia(p=0.009). No significant association was found between VDD and other risk factors such as age, sex , hypertension, diabetes mellitus and smoking. Conclusion : Vitamin D deficiency was noted in majority of the patients undergoing CAG and was found to be significantly associated with the prevalence and severity of CAD. However studies involving larger population are needed to evaluate whether supplementation with vitamin D may help in prevention of atherosclerosis and further development of CAD.